Potensi Pengembangan Pariwisata Halal Berbasis Budaya Melayu di Pulau Penyengat: Analisis SWOT - Nugraha, Yudhi Martha; Awang Pawi, Awang Azman; Hamidon, Nor Azlin binti; Mohd Nasir, Nur Yuhanis binti (Fakultas Ilmu Budaya Universitas Mulawarman, 2025)
Penyengat Island, as one of the centers of Malay-Islamic cultural heritage in Indonesia, holds significant potential to be developed as a culture-based halal tourism destination. This study aims to analyze the potential for halal tourism development on Penyengat Island by leveraging its rich historical legacy and the Islamic values embedded in Malay society, as well as identifying strategic factors through a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). The research employs a qualitative case study approach, with data collected through field observations, in-depth interviews with stakeholders, and reviews of relevant documents. The findings reveal that Penyengat Island possesses strengths such as its rich historical heritage, including the Sultan Riau Mosque, the tomb of Raja Ali Haji, and well-preserved Malay-Islamic cultural traditions. However, weaknesses such as limited infrastructure and a lack of trained human resources in halal tourism pose major challenges. On the other hand, opportunities like the growing global demand for halal tourism and government support can be leveraged for further development. Threats include competition with other halal tourism destinations and the risk of uncontrolled cultural commercialization. Based on these findings, the study proposes development strategies, including infrastructure improvement, human resource training, and integrated promotion to position Penyengat Island as a leading halal tourism destination. The implications of this research not only contribute to local tourism development but also enrich academic literature on culture-based halal tourism. Keywords: halal tourism, Malay culture, Penyengat Island, SWOT analysis, Islamic heritage.